2010
DOI: 10.1521/pedi.2010.24.6.773
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of the Relationship between Diverse Life Events and Specific Personality Disorders in a Sample of Suicide Attempters

Abstract: Personality disorder (PD) increases risk for suicidal behavior. Certain life events (LE) can precipitate suicidal behaviors in patients with PD. A fundamental question is whether specific combinations of LE and PD increase suicidal risk. 446 suicide attempters (SA) were recruited from emergency rooms. We used a healthy control group (n= 515) to identify the best cut-off point for the instrument used to diagnose PD. We used the DSM-IV version of the International Personality Disorder Questionnaire–Screening Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 42 publications
0
32
0
3
Order By: Relevance
“…When the third author arrived to help the second author, the third man decided to pursue analysis to verify and clarify how life events and personality traits contribute to SB [14]. Then he proposed that, rather than biological or genetic variables, life stressors may be the best way to identify psychiatric patients at risk of suicide [15].…”
Section: The Third Manmentioning
confidence: 99%
“…When the third author arrived to help the second author, the third man decided to pursue analysis to verify and clarify how life events and personality traits contribute to SB [14]. Then he proposed that, rather than biological or genetic variables, life stressors may be the best way to identify psychiatric patients at risk of suicide [15].…”
Section: The Third Manmentioning
confidence: 99%
“…6,10,18 Although SB is included in the diagnostic criteria for borderline PD only, individuals with any cluster B PDs appear more inclined to experience stressful life events (e.g., ending a romantic relationship, social rejection, family conflicts, and loss of employment) that may trigger SA. [18][19][20][21] It is important to note that other studies have reported that up to 41.2% of euthymic patients with BD present at least one comorbid PD. Regardless of symptomatic state, cluster B PDs are among the most frequent comorbidities in patients with BD, affecting up to 23% of patients evaluated during euthymia 8 and approximately 30% of patients in whom symptomatic state was not strictly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Se trata de una llamada de atención con diversas finalidades: vengarse de EnriquE EchEburúa alguien, mostrar lo desesperado que se está, buscar ayuda, averiguar si alguien le quiere realmente, huir temporalmente de algo insoportable o mostrar lo mucho que le quiere a una persona. Con frecuencia el sujeto está en una posición ambivalente: desea morir si su vida continúa de la misma manera y desea vivir si se producen cambios significativos en ella (Blasco-Fontecilla et al, 2010).…”
Section: Variantes De La Conducta Suicidaunclassified
“…Acerca de las tensiones vitales múltiples, como la conflictividad familiar, la pérdida de empleo y una situación económica desfavorable, el descubrimiento de un escándalo político o económico, los desengaños amorosos o el fallecimiento reciente de un familiar cercano, éstas tienen un valor predictivo sólo en personalidades vulnerables con tendencias impulsivas y agresivas y con pocas respuestas de afrontamiento (Blasco-Fontecilla et al, 2010 (Mann et al, 2005, modif. ) Figura 1.…”
Section: Signos De Alarma De Riesgo Suicidaunclassified
See 1 more Smart Citation